Սահմանադրությանը հաջորդող երրորդ սերնդի մանկական գրականությունը (1980-2010 թթ.) - Մահմուդ Ֆիրուզիմողադամ (ՀՀ ԳԱԱ հրատ.)
Статья посвящена изучению детской литературы, после конституционного периода Ирана. Предметом исследования, в частности, является детская литература третьего поколения после конституции, которая охватывает период 1980-2010 годов. The article is dedicated to the study of literature for children and young adults after the constitutional revolution. The main objective of this study is a survey of the literature for children and young adults of the third generation of the post-constitutional period from 1980 to 2010.
Keywords: Language and Literature; Children's literature